Analisis Kepuasan Konsumen Dengan Uji Deskriptif Dan PLS Pada Perusahaan Multifinance - Sonny Indrajaya; Jarlest Andini Agustinanda (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
This study aims, to be able to analyze and multi-finance companies in Tangerang City their impact on customer satisfaction. The population for this study were 145 respondents, calculated based on purposive sampling. The method, of collecting data using a survey method, the research instrument using, a questionnaire with a Likert scale. Methods for analyzing data using the SPSS test tool to test descriptive of customer characteristics and Partial Least Square test to obtain hypothesis results. The results, obtained in this study are positive and also very significant, and there are positive results but less significant to customer satisfaction.